Design considerations on wideband envelope termination for high efficiency RF power amplifiers - Chung, S; Ma, R; Teo, K.H (Electronics letters, 2016)
Design approach of wideband envelope termination (ET) for high efficiency RF power amplifiers (PAs) is discussed, considering power loss subject to design constraints including envelope bandwidth, inductor quality factor, and transistor output impedance. Analysis shows that the optimum ET topology depends on the design constraints. For LTE-advanced transmission with 80 MHz channel bandwidth, a novel wideband ET is designed using an AC-terminated third-order LC filter (LCF-ET), providing 3 dB envelope impedance bandwidth of 150 MHz. Measured results demonstrate 1.75 dB envelope power loss and −39.2 dB normalised root-mean-square error with the LTE envelope signals. For the LTE signal with 10.3 dB peak-to-average power ratio, the average power efficiency of an ideal Class-A RF PA with the LCF-ET prototype is calculated as 33.4% from the measured 1.75 dB envelope power loss, which exceeds 4.7% and 24.0% average power efficiency of conventional Class-A and Class-B PAs without ET.